Antioxidant and Antimicrobial activities of Endophytic Fungi isolated from Sesbania grandiflora (L.) Pers. - Pannapa powthong,; Acharawan Thongmee,; Pattra Suntornthiticharoen, (International Journal of Phytomedicine, 2013)
Twenty eight different endophytic fungi were isolated from Sesbania grandiflora (L.) Pers. These endophytic fungal extracts were prepared, using ethyl acetate and evaluated for their phytochemical constituents in vitro. The antibacterial activity of crude extract was done by using broth microdilution and exhibited significant antimicrobial activity against an array of plant pathogenic bacteria included Xanthomonas axonopodis pv. citri, Xanthomonas axonopodis pv. glycines, Xanthomonas campestris pv.campestris and Acidovorax avenae subsp. Avenae range from 125-2000 μg/mL. The total antioxidant capacity was evaluated by using 2, 2-diphenyl-1-picryl-hydrazyl (DPPH) assay ranged from 2.10 x 10-3 to 4.84 x 108 µg /mg extract. The total phenolic content of the fungal extracts was determined by using Folin-Ciocalteu procedures which ranged from 0 to 1730.78 µg gallic acid/mg extract. This is the first report of Sesbania grandiflora (L.) Pers. producing endophytes which have antimicrobial and antioxidant activities. This investigation reveals that the metabolites produced by a variety of endophytic fungi from Sesbania grandiflora (L.) Pers. can be a potential source of novel natural antimicrobials and antioxidants agents.